Morphological and molecular characterisation of Sarcocystis capracanis, Sarcocystis cornagliai and Sarcocystis rossii n. sp. infecting the Alpine ibex (Capra ibex) - Rudaitytė-Lukošienė, Eglė; Rehbein, Steffen; Calero-Bernal, Rafael; Butkauskas, Dalius; Prakas, Petras (Parasites & vectors, 2025)
The cyst-forming coccidia of the genus Sarcocystis (Sarcocystidae) are widespread protists of mammals, particularly of domestic and wild ruminants. Research on genus Sarcocystis in wild members of the subfamily Caprinae is, however, rather limited. Sarcocystis in the Alpine ibex (Capra ibex) have only been investigated in depth once and then solely by morphological techniques. In the current investigation we aimed to morphologically and genetically characterise Sarcocystis species of Alpine ibex in Austria. Sarcocysts detected in the diaphragm and myocardium muscles were morphologically described using light microscopy and transmission electron microscopy (TEM). Isolated sarcocysts were molecularly identified and characterised at the level of the 18S ribosomal RNA (rRNA) gene and cytochrome c oxidase I gene (cox1). The obtained sequences were subjected to phylogenetic analysis. Three Sarcocystis species, namely S. capracanis, S. cornagliai and S. rossii n. sp., were found in Alpine ibex. For the first time, we genetically characterised S. cornagliai, which is most closely related to Sarcocystis species that are transmitted by corvid birds. Sarcocysts of S. rossii n. sp. were found to be ribbon-shaped, with pointed tips. Hair-like protrusions about 5 μm in length were observed on sarcocyst walls. Observation of toluidine blue-stained semi-thin sections revealed that the sarcocyst of S. rossii n. sp. was thin-walled. Using TEM, cyst walls were observed to be similar to type 7a, with thin hair-like villar protrusions on the cyst wall, which were filled with many fine electron-dense granules. The ground substance layer was particularly thin, measuring 0.2-0.4 μm. The cox1 sequences of S. rossii n. sp. had the highest similarity to those of Sarcocystis arieticanis and Sarcocystis hircicanis. Sarcocystis rossii n. sp. had a close phylogenetic relationship with species that use canids as definitive hosts. This study confirms the role of the Alpine ibex as an intermediate host of three Sarcocystis species and sets a new host record for S. capracanis. It also provides the first molecular data on Sarcocystis from Alpine ibex and on S. cornagliai. In addition, a new species, S. rossii, was identified and described. Phylogenetic analyses suggested corvid birds and canids as potential definitive hosts for S. cornagliai and S. rossii n. sp., respectively.